Pengaruh Earning Per Share dan Price Earning Ratio Terhadap Return Saham Pada Perusahaan Industri Wood and Lumber yang Go Public di Bursa Efek Indonesia - Gamal, Ahmad; Gayatri Kartika, Mira; Baramadya (Economics and Sustainable Development, 2024)
The capital market is a vehicle that can mobilise long-term funds from the public to be channelled into productive sectors. The purpose of the capital market in Indonesia is not only to mobilise funds from the public so that they can be channelled into productive sectors, but also to realise income distribution through ownership of company shares. This goal can be achieved gradually with the increasing number and types of securities traded in line with the increasing number of institutions that support the implementation of the capital market. This study aims to determine the effect of earning per share and price earning ratio (PER) on stock returns in Wood and Lumber industry companies that go public on the Indonesia Stock Exchange for the period 2005-2007. The analysis method used in this research is multiple linear regression with SPSS version 12.0. The results of this study can be concluded that: (1) Earning per share has a positive effect on stock returns, because the significance value is smaller than 0.05 and one of the considerations of investors besides risk is the return they will get in the form of a share of net income distributed to shareholders, (2) Price earning ratio has no effect on stock returns, because the significance value is greater than 0.05.